2017
DOI: 10.18203/2320-6012.ijrms20172012
|View full text |Cite
|
Sign up to set email alerts
|

A study on the prevalence of obesity and metabolic syndrome among students of a medical college

Abstract: Background: Obesity is emerging as a serious problem throughout the world. The overall life expectancy is significantly shortened and the quality of life decreased in those who are excessively overweight. Metabolic syndrome (MetS) is characterized by a constellation of individual risk factors of cardiovascular disease. Central obesity is a key feature of this syndrome, reflecting the fact that the syndrome’s prevalence is driven by strong relationship between waist circumference and increasing obesity. Awarene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
3
3
0
Order By: Relevance
“…The present study demonstrated that the prevalence of MetS was higher in males compared to females and males were 3.4 times more likely to develop MetS than females, which is statistically significant. This result agreed with several previous students' studies (10,12,26,34). The higher prevalence of MetS in males can be related to excess body weight, sedentary lifestyles such as physical inactivity and a higher rate of smoking.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The present study demonstrated that the prevalence of MetS was higher in males compared to females and males were 3.4 times more likely to develop MetS than females, which is statistically significant. This result agreed with several previous students' studies (10,12,26,34). The higher prevalence of MetS in males can be related to excess body weight, sedentary lifestyles such as physical inactivity and a higher rate of smoking.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies The association between physical exercise and MetS was not statistically significant. A number of previous studies also agreed with this finding that there is no significant relationship between MetS and physical exercise (10,12,19). In contrast, a previous study found sedentary lifestyle is significantly associated with MetS (8).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…(1) Abdominal obesity (If BMI is > 30 kg/m 2 , central obesity can be assumed and waist circumference does not need to be measured) waist circumference male > 102 cm , female > 88 cm; (2) triglycerides ≥ 150 mg/dL; (3) HDL cholesterol male < 40 mg/dL, female < 50 mg/dL; (4) BP ≥ 130 / ≥ 85 mmHg; (5) fasting glucose ≥ 110 mg/dL. 10,19 Statistical analyses SPSS software version 16.0 was used for analysis. Collected data were described by frequencies and percentages.…”
Section: Definition Of Metabolic Syndrome (Mets)mentioning
confidence: 99%